(untitled) (Plant Bulletin, 2025)
Monocropping and continuous use of exhaustive crop which ultimate result soil degradation such as reduction of soil organic carbon, leaching and loss of nutrient and soil erosion. The intercropping has the potential to reduce soil degradation by leveraging complementarity and resource utilization between different crop species and increase crop productivity and carbon sequestration.A study was designed with the three crops.i.e. wheat, linseed and chickpea with the treatments i.e. T1 (sole wheat), T2 (sole linseed), T3 (sole chickpea), T4 (chickpea-linseed), T5 (chickpea-wheat), T6 (wheat-linseed) and T7 (linseed-chickpea-wheat) in randomized complete design with three replication. The results showed that intercropping concurrently in T4, T6 and T7 has a positive outcome in terms of land utilization and yield advantages by having LER values 1.025, 1.185 and 1.75 respectively. And these treatments have k>1 and positive value of AYL further validate the benefit of cultivating of these crop species together. Conversely, the T5 has no yield and benefit and has inefficiency in land utilization as evident by LER 0.873 & k=0.767 and negative value of AYL. From a statistical standpoint, intercropping has no discernible effect (p<0.05) on vegetative growth characteristics of the individual crops when they are cultivated as intercrops other than the no. of pods/plant in chickpea (P=0.0107). According to the findings of this study, the strategic adoption of diversified intercropping systems, such as combining wheat with linseed, chickpea with linseed or linseed-chickpea-wheat, can play a crucial role in supporting agricultural intensification in areas primarily dominated by smallholder farmers. Moreover, these intercropping systems have the potential to provide ecological advantages and contribute positively to the existing monocropping system.